2019
DOI: 10.1111/oik.06376
|View full text |Cite
|
Sign up to set email alerts
|

Not all disturbances are created equal: disturbance magnitude affects predator–prey populations more than disturbance frequency

Abstract: Disturbance plays a key role in ecological structure and function. Two important and often studied components of disturbance are frequency and magnitude. Despite the potential for non‐linear interactions between frequency and magnitude, their effects are often assumed to combine in a linear manner. Additionally, studies of disturbance have mainly examined effects on species diversity and competitive interactions within a single trophic level, with less focus on exploitative interactions across trophic levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…For example, in systems with tightly coupled consumer-resource or competitive species interactions, the nature of those interactions will also affect recovery trajectories (e.g. Commander & White, 2020). Alternatively, a system with multiple attractors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in systems with tightly coupled consumer-resource or competitive species interactions, the nature of those interactions will also affect recovery trajectories (e.g. Commander & White, 2020). Alternatively, a system with multiple attractors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Powell and Wells (2011) and Christiansen et al (2016) reported a rapid increase in conditioning to human interactions through food provisioning beginning in 2005-2006 resulting, at least in part, from the effects of red tide on fish populations and community structure in Sarasota Bay (see Gannon et al, 2009). Understanding how different red tide events affect the dynamics and persistence of populations linked by predator-prey interactions, including possible temporary alterations in the strength or rate of interspecific interactions within a community without directly changing abundances, is critical for effective management efforts (Commander and White, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, chronic ecological disturbances can negatively impact environmental conditions, resulting in ecosystems with lower resilience to perturbation events, and greater risk of surpassing a tipping point between stable states (Scheffer et al, 2001;Lewis et al, 2021). Much work has focused on the dynamics of single species or guilds of species at the same trophic level, therefore the direct and indirect disturbance effects on the dynamics of populations linked by predator-prey interactions, across different trophic levels, are not as well understood (Commander and White, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Using dynamic models, Commander & White, 2020 showed the effects of various disturbances based on different predator–prey population dynamics, we hypothesized predator–prey dynamics over time after an ECE. An ECE near or at the peak of growth in populations of predator and prey (purple arrow) could result in a decrease in the predator's population growth and an increase in prey's population growth.…”
Section: Population‐level Timingmentioning
confidence: 99%
“…The timing of an ECE will be important when considering the consequences of extreme weather on populations that cycle with another species, such as in predator–prey dynamics. In a predator–prey scenario, we may observe that the ECE will first alter the dynamics of the prey or the predator, with the magnitude of the effects depending on the timing of the populations, later cascading to consequences on predator–prey dynamics (Commander & White, 2020) (Figure 4). Finally, in a population that has non‐stationary dynamics we could observe various scenarios where the timing of ECE can have unpredictable effects or no effects.…”
Section: Population‐level Timingmentioning
confidence: 99%